KOMPENSASI SEBAGAI PENYEMANGAT KERJA UNTUK MENINGKATKAN KINERJA KARYAWAN (STUDI KONSEP KOMPENSASI DAN KINERJA KARYAWAN) - Setya Prihatiningtyas (Aplikasi Administrasi: Media Analisa Masalah Administrasi, 2016)
The more intense the level of business competition today, resulting in the company faced with the challenge to be able to maintain the survival of his company. therefore companies must be able to compete and one tool that can be used by the company is by providing compensation, both in the form of financial compensation and non-financial compensation. if the compensation program is perceived to be fair and competitive by employees, it will be easier to retain employees and encourage employees to improve their performance so that their performance can improve and companies are able to produce products at competitive prices. companies not only excel in business competition alone, but also able to maintain the survival of the company, even able to increase profits and expand its business.